Simple Synthesis of Cellulose Triacetate from HVS Paper Waste and Its Application for Optode - Arif, Zulhan; Fendy; Akhmad Aghzath, Ananjaya; Saprudin, Deden; Rohaeti, Eti (Indonesian Journal of Chemical Studies, 2024)
The optode membrane is a membrane that can identify ions in an aqueous solution. One of the most widely used optode membranes is cellulose triacetate based. Cellulose triacetate (CTA) has the characteristics of hydrophobic, transparent, elastic, and affordable. There are sources of cellulose triacetate that can be utilized and waste paper is one of them. Waste paper is extracted to obtain the cellulose, then by acetylization reaction to produce cellulose triacetate. The resultant cellulose triacetate has a degree of substitution (DS) of 2.89 and an acetyl group percentage (% AG) of 43.64. The standard and synthesized CTA optode membrane are tested for performance with various parameters, ie optimum pH, optimum immersion time, working range, limit of detection (LOD), and limit of quantification (LOQ). The standard CTA optode membranes and synthesized worked at pH 3 and 4 with optimum immersion time for 15 min, respectively. The optode produced a linear response in detecting Cr(VI) ion in the concentration range of 0.02-1 mg/L for standard CTA with an R2 of 0.9726 and 1-25 mg/L for synthesized CTA with an R2 of 0.9764, The limit of detection (LOD) and limit of quantitation (LOQ) were 0.0015 mg/L and 0.0051 mg/L for standard CTA, while 0.0224 mg/L and 0.0749 mg/L for synthesis CTA respectively. Since both optode membranes' performance test results are adequate, the synthesis results of CTA optode membranes can be employed as one source of cellulose triacetate.